Analysis Of Staffing Strategies In Startup Companies: A Qualitative Study In Startup Companies In Jakarta, Indonesia - Maulidya Niken Widyasari; Aryana Satrya (Green Publisher Indonesia, 2024)
The purpose of this research is to understand the planning, implementation, and evaluation of staffing strategies by startup companies to ensure their success. This study employs a qualitative approach using a case study method. Research data were obtained through observation at one small startup company, namely Investify, and in-depth interviews with 16 informants, including HR staff, HR Managers, and one CEO of a startup company. Data were coded using NVivo 12 software. The research findings reveal that staffing strategies involve several stages, including selecting job posting channels, candidate screening, and offering incentives to potential employees. The limitations lie in the research scope, focused only on startups in Jakarta, and potential bias in data interpretation. Using these research findings, practitioners can enhance workforce management effectiveness by reinforcing the company's brand through cultural communication, exploring diverse recruitment channels, and improving employee selection methods. The originality and value of this research lie in exploring workforce strategies in Jakarta's startup companies, providing insights into recruitment and selection processes that can enhance staffing strategies in startup companies.